- Pencabutan Keterangan Terdakwa yang Termuat Dalam Berita Acara Pemeriksaan Tingkat Penyidikan Pada Proses Persidangan di Pengadilan - Arnaldo Vinerdi; Setiyono (Reformasi Hukum Trisakti, 2023)
Evidence is quite an important part of a trial examination, so as a judge you must be careful in carrying out the judge's considerations. However, in the evidentiary process, sometimes there are obstacles, such as the defendant retracting his statement in the BAP. This research formulates the problem of how legal analysis is related to the considerations of the cassation judge in narcotics cases found in Decision Number 399/Pid.Sus/2021/PN Plk and how the analysis of the defendant's testimony is considered as part of the evidence.Normative juridical is used as a method in this research. The results of this research are that the defendant withdrawing his statement in the BAP certainly cannot be used as the main reason for the judge's decision in a case and the investigative witness can be used as evidence in the trial but not as evidence that can be confronted with the defendant's statement retracting the BAP, the investigative witness is only one part of the evidence. which can convince the panel of judges to assess the defendant's guilt.